2023
DOI: 10.1037/pha0000566
|View full text |Cite
|
Sign up to set email alerts
|

Binding potential changes of SERT in patients with depression are associated with remission: A prospective [¹²³I]β-CIT-SPECT study.

Abstract: The status of remission in patients with major depressive disorder treated with selective serotonin reuptake inhibitors (SSRIs) is mostly evaluated with clinical rating scales. Morphological correlates of the remission status remain a rare event. Addressing this challenge, we investigated functional correlates of remission by assessment of serotonin and dopamine transporter availability (SERT and DAT) using single-photon emission computed tomography (SPECT). Our purpose was to identify changes in the SERT/DAT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…However, the results of the double-blind trial with escitalopram of Zoons et al showed that a 6-week treatment course with 10 mg escitalopram daily did not influence the DAT binding of [ 123 I]I-FP-CIT in 8 patients with cervical dystonia [ 95 ]. Krause and colleagues did not show a significant influence of 6 weeks treatment with escitalopram on striatal [ 123 I]I-β-CIT binding in a group of 19 patients with major depression [ 96 ]. Since (sub)chronic treatment with escitalopram induces no significant decrease in striatal DAT binding and possible increases in binding are observed both in the putamen and caudate nucleus, it is unlikely that the use of this SSRI will negatively influence a visual read of DAT imaging.…”
Section: Resultsmentioning
confidence: 99%
“…However, the results of the double-blind trial with escitalopram of Zoons et al showed that a 6-week treatment course with 10 mg escitalopram daily did not influence the DAT binding of [ 123 I]I-FP-CIT in 8 patients with cervical dystonia [ 95 ]. Krause and colleagues did not show a significant influence of 6 weeks treatment with escitalopram on striatal [ 123 I]I-β-CIT binding in a group of 19 patients with major depression [ 96 ]. Since (sub)chronic treatment with escitalopram induces no significant decrease in striatal DAT binding and possible increases in binding are observed both in the putamen and caudate nucleus, it is unlikely that the use of this SSRI will negatively influence a visual read of DAT imaging.…”
Section: Resultsmentioning
confidence: 99%